Non-Thermal Plasma, as a New Physicochemical Source, to Induce Redox Imbalance and Subsequent Cell Death in Liver Cancer Cell Lines - Smolková, Barbora; Lunova, Mariia; Lynnyk, Anna; Uzhytchak, Mariia; Churpita, Olexander; Jirsa, Milan; Kubinová, Šárka; Lunov, Oleg; Dejneka, Alexandr (Cellular physiology and biochemistry, 2019)
BACKGROUND/AIMS: Alteration of cancer cell redox status has been recognized as a promising therapeutic implication. In recent years, the emerged field of non-thermal plasma (NTP) has shown considerable promise in various biomedical applications, including cancer therapy. However, understanding the molecular mechanisms procuring cellular responses remains incomplete. Thus, the aim of this study was a rigorous biochemical analysis of interactions between NTP and liver cancer cells. METHODS: The concept was validated using three different cell lines. We provide several distinct lines of evidence to support our findings; we use various methods (epifluorescent and confocal microscopy, clonogenic and cytotoxicity assays, Western blotting, pharmacological inhibition studies, etc.). RESULTS: We assessed the influence of NTP on three human liver cancer cell lines (Huh7, Alexander and HepG2). NTP treatment resulted in higher anti-proliferative effect against Alexander and Huh7 relative to HepG2. Our data clearly showed that the NTP-mediated alternation of mitochondrial membrane potential and dynamics led to ROS-mediated apoptosis in Huh7 and Alexander cells. Interestingly, plasma treatment resulted in p53 down-regulation in Huh7 cells. High levels of Bcl-2 protein expression in HepG2 resulted in their resistance in response to oxidative stress- mediated by plasma. CONCLUSION: We show thoroughly time- and dose-dependent kinetics of ROS accumulation in HCC cells. Furthermore, we show nuclear compartmentalization of the superoxide anion triggered by NTP. NTP induced apoptotic death in Huh7 liver cancer cells via simultaneous downregulation of mutated p53, pSTAT1 and STAT1. Contrary, hydrogen peroxide treatment results in autophagic cell death. We disclosed detailed mechanisms of NTP-mediated alteration of redox signalling in liver cancer cells.
Keywords: Oxidation-Reduction; reaktivní formy kyslíku; regulace genové exprese u nádorů; Reactive Oxygen Species; Tumor Suppressor Protein p53; p53; buňky Hep G2; Hep G2 Cells; Apoptosis, Non-thermal plasma; Humans; down regulace; Stress resistance; Carcinoma, Hepatocellular; Plasma Gases; Oxidative stress; oxidace-redukce; plazmové plyny; Liver Neoplasms; Reactive oxygen species; Down-Regulation; buněčná smrt; Gene Expression Regulation, Neoplastic; Cell Death; nádory jater; lidé; nádorový supresorový protein p53; hepatocelulární karcinom